Enhancing Fifth Grade IPAS Learning Outcomes Using the Role Playing Model at SDN 5 Sindue Tobata - Rajes, Sagma; Latief, Juraid Abdul; Rizal, Rizal; Firmansyah, Arif; Pahriadi, Pahriadi (Journal of Educational Sciences, 2025)
This classroom action research aimed to improve student learning outcomes in the IPAS subject by implementing the Role Playing learning model. The study was conducted in two cycles, each consisting of four stages: planning, action implementation, observation, and reflection. The research subjects were 20 fifth-grade students of SDN 5 Sindue Tobata in the 2024/2025 academic year, comprising 10 boys and 10 girls. Data collection techniques included observation, learning outcome tests, and documentation. The data were analyzed using a descriptive quantitative and qualitative approach. The findings showed a significant improvement in student learning outcomes after applying the Role Playing model. In the first cycle, the class average score increased from 55.5 to 66, with a learning mastery percentage of 65%. In the second cycle, the average score rose to 80, with a mastery level of 85%. Additionally, the model enhanced student engagement and participation, creating a more enjoyable and meaningful learning environment. These results indicate that the Role Playing model is effective in improving student achievement in IPAS and can be recommended as a classroom implementation strategy in similar educational contexts.